Modification of Rhizosphere Microbial Communities: A Possible Mechanism of Plant Growth Promoting Rhizobacteria Enhancing Plant Growth and Fitness - Kong, Zhaoyu; Liu, Hongguang (Frontiers in Plant Science, 2022)
Plant beneficial bacteria, defined as plant growth-promoting rhizobacteria (PGPR), play a crucial role in plants’ growth, stress tolerance and disease prevention. In association with the rhizosphere of plants, PGPR facilitate plant growth and development either directly or indirectly through multiple mechanisms, including increasing available mineral nutrients, moderating phytohormone levels and acting as biocontrol agents of phytopathogens. It is generally accepted that the effectiveness of PGPR inoculants is associated with their ability to colonize, survive and persist, as well as the complex network of interactions in the rhizosphere. Despite the promising plant growth promotion results commonly reported and mostly attributed to phytohormones or other organic compounds produced by PGPR inoculants, little information is available on the potential mechanisms underlying such positive effects via modifying rhizosphere microbial community and soil functionality. To date, increasing attention has been paid to the effects of PGPR inoculants on soil microbial community and soil functioning. In this review, we overviewed the effects of PGPR inoculants on rhizosphere microbial ecology and soil function, hypothesizing that PGPR may indirectly promote plant growth and health via modifying the composition and functioning of rhizosphere microbial community, and highlighting the further directions for investigating the role of PGPR in rhizosphere from an ecological perspective.